Process of cement production in Nepal - Pandey, Paresh Raj; Banskota, Narayan (Bulletin of the Department of Geology, 2008)
This paper describes general process of cement production from exploration of limestone deposit to production of clinker and finally cement. Exploration of limestone comprises area selection, target definition, reserve calculation, resource evaluation and reserve definition. After exploration, mining is taken up. Quarried limestone is stockpiled and then is blended with other raw material like clay/shale, silica, iron ore in required proportion. The blended material is then heated at high temperature upto 1400-1450°C in a kiln to produce clinker. The clinker is grinned along with 3-5% gypsum to produce cement. doi: 10.3126/bdg.v11i0.1545 Bulletin of the Department of Geology, Tribhuvan University, Kathmandu, Nepal, Vol. 11, 2008, pp. 71-78